CLASSROOM MANAGEMENT IN SECONDARY SCHOOLS IN NIGERIA: ROLE OF THE TEACHER - SUDETU OSENI; ABDUL-SALAMI NASIRU ELAMAH; OLAJIRE AFUSAT ORINIOWO (International Studies Journal)
The ability to manage a classroom effectively is increasingly becoming a fundamental need in any quest for effective teaching and learning worldwide.  In Nigeria, the urge is about the same as the issue of effective classroom management has become crucial and recurring in educational discourse. Teachers play vital roles in the lives of the students in their classrooms. Effective teaching and learning can hardly be noticed in a poorly managed classroom. A well-managed classroom requires a teacher who is characterized by high knowledge of content, context, pedagogy and personal discipline. This paper, therefore, examined classroom management in Nigerian Secondary Schools and the role the teacher has to play.  Various discussions were given on these roles amongst which are:  the teacher having good knowledge of his subject so as to manage the classroom effectively; the teacher making use of varied methods of teaching in order to make the classroom interesting; and the teacher always comporting himself in the classroom.  It was suggested amongst others that teachers should encourage their students in the classroom by praising them verbally as this will motivate them to learn more.  Also, that management of schools should improve the classroom management skills and approaches of teachers by setting up many seminars/workshops.